Sensitivity of the African neuropsychology battery memory subtests and learning slopes in discriminating APOE 4 and amyloid pathology in adult individuals in the Democratic Republic of Congo - Ikanga, Jean; Patrick, Sarah D.; Schwinne, Megan; Patel, Saranya Sundaram; Epenge, Emmanuel; Gikelekele, Guy; Tshengele, Nathan; Kavugho, Immaculee; Mampunza, Samuel; Yarasheski, Kevin E.; Teunissen, Charlotte E.; Stringer, Anthony; et al. (Frontiers in Neurology, 2024)
The current study examined the sensitivity of two memory subtests and their corresponding learning slope metrics derived from the African Neuropsychology Battery (ANB) to detect amyloid pathology and APOE4 status in adults from Kinshasa, the Democratic Republic of the Congo.Methods: 85 participants were classified for the presence of β-amyloid pathology and based on allelic presence of APOE4 using Simoa. All participants were screened using CSID and AQ, underwent verbal and visuospatial memory testing from ANB, and provided blood samples for plasma A42, A40, and APOE proteotype. Pearson correlation, linear and logistic regression were conducted to compare amyloid pathology and APOE4 status with derived learning scores, including initial learning, raw learning score, learning over trials, and learning ratio.Results: Our sample included 35 amyloid positive and 44 amyloid negative individuals as well as 42 without and 39 with APOE4. All ROC AUC ranges for the prediction of amyloid pathology based on learning scores were low, ranging between 0.56-0.70 (95% CI ranging from 0.44-0.82). The sensitivity of all the scores ranged between 54.3-88.6, with some learning metrics demonstrating good sensitivity. Regarding APOE4 prediction, all AUC values ranged between 0.60-0.69, with all sensitivity measures ranging between 53.8-89.7. There were minimal differences in the AUC values across learning slope metrics, largely due to the lack of ceiling effects in this sample.Discussion: This study demonstrates that some ANB memory subtests and learning slope metrics can discriminate those that are normal from those with amyloid pathology and those with and without APOE4, consistent with findings reported in Western populations.